THE PARADIGM OF INCLUSIVE EDUCATION FROM THE PERSPECTIVE OF ISLAMIC EDUCATION: Dynamics in Islamic Schools in Lombok - Murdianto Murdianto (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2024)
This research examines the implementation of the inclusive education paradigm in the context of Islamic education in Islamic schools in Lombok. Inclusive education has become a global focus in the effort to achieve educational equality, yet its implementation within the context of Islamic education still faces various challenges. Using a qualitative approach with a case study method, this research investigates how Islamic schools in Lombok integrate the principles of inclusion within the framework of Islamic education. The research findings indicate a complex dynamic in aligning Islamic values with inclusive education practices. The main challenges include limited resources, a lack of teacher training, and socio-cultural stereotypes. However, promising local innovations have also been found in adapting the curriculum and teaching methods to accommodate student diversity. This study reveals that despite the gap between policy and implementation, Islamic schools in Lombok show positive progress in adopting inclusive practices. This research contributes to a deeper understanding of the intersection between inclusive education and Islamic education while highlighting the importance of contextualizing inclusive education policies within specific cultural and religious settings.